Strategi Pemulihan Kondisi Ekonomi Nasional Pada Masa Pandemi Covid-19 dalam UMKM Kabupaten Tulungagung - Muhammad Iqbal Nazwar; Saiful Anwar (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2022)
March 2, 2020, is the day of obstacles for all sectors in Indonesia, especially the national economic sector. The tourism sector, industrial sector, mining sector, agriculture sector and other essential sectors experienced a tremendous downturn. All recovery efforts were made to restore industries that played a significant role in developing the national economy. Based on the phenomena that occurred, this article discusses how the strategy for restoring national economic conditions during the COVID-19 pandemic impacts UMKM. Based on the topic raised from the facts that happened, the research method was carried out quantitatively-qualitatively. This method is based on positivist thinking which seeks to explain causality in the phenomena. In addition, the phenomenological school of thought is also applied in understanding the wonders of social life. The data presented in the form of accurate quantitative data found in the reference literacy process and qualitative data obtained based on literacy studies.